Friends Reconsidered: Cultural Politics, Intergenerationality, and Afterlives. (December 2018) - Cobb, Shelley; Ewen, Neil; Hamad, Hannah
With the passing in 2014 of the twentieth anniversary of its debut episode, the iconic millennial sitcom Friends retains a rare cultural currency and remains a crucial reference point for understanding the concerns of Generation X. This special issue, therefore, interrogates the contemporary and historical significance of Friends as a popular sitcom that reflected and obfuscated American fin de siècle anxieties at the time, and considers the lasting resonance of its cultural afterlife. Its abiding impact as millennial cultural touchstone can be seen in its persistent ability to find new generations of viewers and its manifest influence on myriad extratextual phenomena.